2012
DOI: 10.1097/mnm.0b013e3283570fb8
|View full text |Cite
|
Sign up to set email alerts
|

Nasolacrimal duct obstruction as a complication of iodine-131 therapy in patients with thyroid cancer

Abstract: NLDO may be considered as a side effect of I-131 therapy, especially with a cumulative dose of 11.1 GBq or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
10
0
9
Order By: Relevance
“…Other possible causes (allergic or viral conjunctivitis, keratoconjunctivitis sicca, trichiasis, canaliculitis, iritis, and functional causes of excessive tears) should be ruled out to reach a definitive diagnosis of 131 I therapy-acquired NLDO. 14 131 I therapy-acquired NLDO is defined as: 1) the presence of NLDO in 131 I therapy-treated patients; 2) an 131 I dose–NLDO relationship; 3) immediate onset of symptoms after 131 I therapy; and 4) the bilateral nature of NLDO in most of cases. CT dacryography using diluted contrast medium was found to be an easy and highly sensitive tool to evaluate NLDO in our cohort, which endorsed the findings of Garcier et al 15…”
Section: Discussionmentioning
confidence: 99%
“…Other possible causes (allergic or viral conjunctivitis, keratoconjunctivitis sicca, trichiasis, canaliculitis, iritis, and functional causes of excessive tears) should be ruled out to reach a definitive diagnosis of 131 I therapy-acquired NLDO. 14 131 I therapy-acquired NLDO is defined as: 1) the presence of NLDO in 131 I therapy-treated patients; 2) an 131 I dose–NLDO relationship; 3) immediate onset of symptoms after 131 I therapy; and 4) the bilateral nature of NLDO in most of cases. CT dacryography using diluted contrast medium was found to be an easy and highly sensitive tool to evaluate NLDO in our cohort, which endorsed the findings of Garcier et al 15…”
Section: Discussionmentioning
confidence: 99%
“…Nasolacrimal obstruction (NLDO) after RAIT has been reported by several studies [90][91][92][93][94]. RAI uptake by Conclusion RAIT for DTC generally causes relatively mild shortterm toxicity and, infrequently, serious complications.…”
Section: Methodsmentioning
confidence: 99%
“…However, our study on the possible hazard of 131 I on the lacrimal drainage system, performed using dacryoscintigraphy, which has been proved to be a valuable method for this purpose [95], showed that 18% of exposed eyes had evidence of NLDO on scintigraphic images. The frequency of complete NLDO significantly increases when the cumulative dose of radioiodine exceeds 11.1 GBq (300 mCi) [90].…”
Section: Dry Eyementioning
confidence: 99%
See 1 more Smart Citation
“…Fard-Esfahani et al 48 evaluated nasolacrimal duct obstruction as a complication ofiodine-131 therapy in 81 patients with thyroid cancer. A total of 17 age-matched sex-matched individuals were selected as control group.…”
Section: Local Clinical Evaluationsmentioning
confidence: 99%